PAULO COELHO’S VERONIKA DECIDES TO DIE: SEMIOTICS STUDY: Received: 23rd November 2023; Revised: 8th January 2023, 17th February 2023, 04th April 2023; Accepted: 11th April 2023 - Al-dihaymawee , Doaa Taher (PEOPLE: International Journal of Social Sciences, 2023)
Veronika Decides to Die is one of Paulo Coelho’s best-selling novels, through which he describes in details what is happening inside the wall of mental hospitals. The novel was first published in 1998. The researcher selects this novel as there is no study has been done so far in analyzing Veronika Decides to Die from a semiotics viewpoint. There are two main Semiotics theories, one is represented by the Swiss linguistics Ferdinand de Saussure and another is represented by the American philosopher Charles Sanders Peirce. Peirce’s triadic theory of icon, index and symbol. The latter has been selected as a tool in answering the research question of: What are the main signs in Coelho’s Veronika Decides to Die?